Draft Fourth Five Year Plan (1966-71) Part-II Union Territory of Pondicherry - Planning Commission (Planning Commission, 1966)
Summary statement of Plan outlay proposed 19S6-71 - Territory Plans Distribution of outlay under selected sub heads - Territory Plans Schemes requiring Foreign Exchange Targets for selected programmes.
Union Territory of Pondicherry